In vivo hair growth promotion activity of gel containing niosomes loaded with the Oryza sativa bran fraction (OSF3) - Manosroi A. (2014)
Gel containing fraction No. 3 of Oryza sativa bran extract (OSF3) loaded in CTAB niosomes (gel OSF3 niosomes) showed similar in vivo hair growth promoting activity and anagen induction effect in C57BL/6 mice model to OSF3 niosomes. Gel OSF3 niosomes exhibited lower toxicity both cytotoxicity on human skin fibroblasts and in vivo irritation test on rabbit skin than OSF3 niosomes owing to the gel structure that may protect the skin from the toxicity of the cationic niosomes. Moreover, gel OSF3 niosomes demonstrated higher in vivo hair growth promotion activity with the hair growth score of 3.0 and the mean hair length of 6.9 mm at day 21st of the application than the standard dutasteride at 1.50 and 1.92 times, respectively. This study has suggested that not only the toxicity and in vivo hair growth promotion activity of OSF3 loaded in cationic niosomes can be improved when incorporated in gel formulation but also the potential of OSF3 to be used for anti-hair loss by loading in niosomes. © 2012 American Scientific Publishers. All rights reserved.